Polemik Halal Tourism dalam Analisis Ekologi Budaya di Desa Wisata Tomok Kabupaten Samosir - Andriansyah, Dedi; Simbolon, Windo Putra Sanjaya; Manik, Jeremia; Ardiansyah, Ardiansyah (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2024)
This research aims to determine the background to the rejection of halal discourse, the socio-cultural adaptation of the Toba Batak local community to Muslim immigrants, namely the Javanese and Minang ethnic groups in the Tomok Tourism Village, Simanindo District, Samosir Regency. The theory used as an approach in research is Julian Steward's cultural ecology. Cultural ecological adaptation is a process of continuous adjustment carried out by humans with their environment which prioritizes the application of ecological concepts and principles to aspects of social life that are truly appropriate to the local community. This research method is qualitative research. Qualitative data collection techniques include participant observation, ethnographic interviews. The research results show that the background to the rejection of halal tourism discourse is formulated in three aspects: 1) structural, namely the ambiguity of the concept of halal tourism vertically, 2) cultural, namely threats to the ecological and cultural ecosystem, 3) social processes, namely disruption of the social ecosystem. The socio-cultural adaptation process is formed through: 1) culture core, namely the establishment of economic ties, 2) social integration, namely the involvement of Javanese and Minang ethnic immigrants in traditional structures, 3) cultural features, namely social participation and the creation of reciprocal relationships between the local Toba Batak community and ethnic immigrants, 4) environmental exploitation, namely the concept of spatial planning that forms regional typologies, 5) environmental subsistence, namely the cultural stability of the Batak Toba philosophy of dalihan na tolu.